Assessments of plasma ghrelin levels in the early stages of parkinson's disease. Issue 10 (6th July 2017) - Song, Ning; Wang, Weiwei; Jia, Fengjv; Du, Xixun; Xie, Anmu; He, Qing; Shen, Xiaoli; Zhang, Jing; Rogers, Jack T.; Xie, Junxia; Jiang, Hong
ABSTRACT: Background: Gastrointestinal symptoms are early events in Parkinson's disease (PD). The gastrointestinal hormone ghrelin was neuroprotective in the nigrostriatal dopamine system. The objective of this study was to assess ghrelin levels in the early stages of PD. Methods: Plasma was collected in the fasting state in 291 PD patients in stages 1‐3 and 303 age‐ and sex‐matched healthy controls. Additional samples were taken in the glucose response test to assess nutrition‐related ghrelin levels in 20 PD patients and 20 healthy controls. The enzyme‐linked immunosorbent assay was used to measure total and active plasma ghrelin levels. Results: We reported that total and active plasma ghrelin levels were decreased in PD, although there was no difference across progressive PD stages. Postprandial ghrelin suppression and preprandial peak responses were both attenuated in PD. Conclusions: Plasma ghrelin levels were decreased in PD; however, this event might be irrelevant to PD progression. Ghrelin responses to meals were also impaired in PD. © 2017 International Parkinson and Movement Disorder Society